2021
DOI: 10.1021/acsestengg.1c00272
|View full text |Cite
|
Sign up to set email alerts
|

Using Adhesives to Capture Microplastics from Water

Abstract: Microplastic pollution is omnipresenthaving been found in our land, air, food, and water. Over the last two decades, both identifying microplastics and sleuthing their sources has been a major research focus. Moving forward, the next goal should be remediation. Although removing microplastics from the environment is impractical, developing methods that prevent their release into the environment is essential. Herein, we report an approach for removing microplastics from water using a pressuresensitive adhesive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Consequently, the adhesives can, over time, move across and off the coated substrate, leading to uneven coatings and shedding. We observed this undesirable phenomenon in our previous system 23 with P EH -coated zirconium silicate beads (Fig. 1A and Fig.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…Consequently, the adhesives can, over time, move across and off the coated substrate, leading to uneven coatings and shedding. We observed this undesirable phenomenon in our previous system 23 with P EH -coated zirconium silicate beads (Fig. 1A and Fig.…”
Section: Resultsmentioning
confidence: 65%
“…Once deposited, the solvent quickly evaporates, producing a more even coating than the original solvent-casting methods. 23 The coated SS beads were stirred in an aqueous suspension of microplastics for 18 h to compare to the zirconium silicate beads. The SS coatings appeared more stable via scanning electron microscopy (SEM), though some evidence of adhesive migration was still visible (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chazovachii et al. indicated that shaking zirconium silicate beads coated with poly(2-ethylhexyl acrylate) in aqueous suspensions containing PS−MPs (10 μm) could remove up to 99% of the MPs within 5 min[ 52 ]. Solar energy was used to drive the removal of MPs in aquatic environments, in which the sunlight was focused by high-density glass spheres to induce convection and form microbubbles at the interface.…”
Section: Enrichment and Removal Technologies Of Microplastics In Aqua...mentioning
confidence: 99%
“…Currently this method has only been used to compare the degradative effects of MP digestion methods, but represents a promising technique that can be adapted to other uses. Adhesive coated glass slides and beads have also been validated to successfully extract MPs comprised of PS, PE, PA, PET and micronized rubber from an aqueous matrix [168]. However, this method may not be well adapted to MNP removal from complex matrices.…”
Section: Soft Extraction Protocols and Reference Materialsmentioning
confidence: 99%